Mismatched canal conservation and the authorized heritage discourse in urban China: a case of the Hangzhou Section of the Grand Canal. Issue 2 (1st February 2020) - Zhang, Mengke; Lenzer, James H.
ABSTRACT: Even before receiving the World Heritage designation in 2014, the Grand Canal in China presented a challenging conservation task. Chinese governments lacked an appropriate evaluation system and conservation principles for this particular type of heritage asset; rather, they tended to follow international institutional guidelines. This paper discusses the ideological and institutional factors in the authorized heritage discourse (AHD) framework to address current strategies and problems in conserving the Hangzhou Section of the Grand Canal. From an ideological perspective, the paper analyses the consequences of dominant Western values in regulating Chinese heritage practices, exemplified by the UNESCO evaluation system; from an institutional perspective, it identifies governments' tendency to impose strict control over canal conservation projects. This paper argues that the existing hegemonic conservation approaches have failed to bring out the unique values of the Grand Canal. In addition, local governments focus more on reaping the economic benefits of heritage than on conserving the heritage in terms of sustainability, and local people's interests tend to be dismissed in these processes.